2017
DOI: 10.3389/fpsyg.2017.01208
|View full text |Cite
|
Sign up to set email alerts
|

Facial Contrast Is a Cross-Cultural Cue for Perceiving Age

Abstract: Age is a fundamental social dimension and a youthful appearance is of importance for many individuals, perhaps because it is a relevant predictor of aspects of health, facial attractiveness and general well-being. We recently showed that facial contrast—the color and luminance difference between facial features and the surrounding skin—is age-related and a cue to age perception of Caucasian women. Specifically, aspects of facial contrast decrease with age in Caucasian women, and Caucasian female faces with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…Facial contrastthe colour and luminance contrast between the facial features and the surrounding skin is positively associated with attractiveness (Russell, 2003;St€ ormer & Alvarez, 2016) and is increased through typical makeup use (Etcoff et al, 2011;Jones et al, 2015;Russell, 2009;Stephen & McKeegan, 2010). Aspects of facial contrast are sexually dimorphic, being greater in female than male faces (Jones et al, 2015;Russell, 2009;Russell, Kramer, & Jones, 2017), while other aspects decline with age and are used as cues for perceiving age and health from the face (Porcheron, Mauger, & Russell, 2013;Porcheron et al, 2017;Russell et al, 2016Russell et al, , 2017. Theorists have proposed that facial feature size mediates the effect of makeup on attractiveness (Bruce & Young, 1986;Morris, 1977Morris, , 2002Perrett, 2010;Zebrowitz, 1997), and recent work has shown that makeup does indeed make the eyes and eyebrows appear larger (Morikawa, Matsushita, Tomita, & Yamanami, 2015).…”
mentioning
confidence: 99%
“…Facial contrastthe colour and luminance contrast between the facial features and the surrounding skin is positively associated with attractiveness (Russell, 2003;St€ ormer & Alvarez, 2016) and is increased through typical makeup use (Etcoff et al, 2011;Jones et al, 2015;Russell, 2009;Stephen & McKeegan, 2010). Aspects of facial contrast are sexually dimorphic, being greater in female than male faces (Jones et al, 2015;Russell, 2009;Russell, Kramer, & Jones, 2017), while other aspects decline with age and are used as cues for perceiving age and health from the face (Porcheron, Mauger, & Russell, 2013;Porcheron et al, 2017;Russell et al, 2016Russell et al, , 2017. Theorists have proposed that facial feature size mediates the effect of makeup on attractiveness (Bruce & Young, 1986;Morris, 1977Morris, , 2002Perrett, 2010;Zebrowitz, 1997), and recent work has shown that makeup does indeed make the eyes and eyebrows appear larger (Morikawa, Matsushita, Tomita, & Yamanami, 2015).…”
mentioning
confidence: 99%
“…According to current research [13][14][15][16] and universal opinion, skin color definitely affects perceived age. Fink et al, in a study of 170 British women, randomly showed their pictures to participants.…”
Section: Skin Colormentioning
confidence: 94%
“…The full-face images were manipulated using Adobe Photoshop CS4 in Lab color mode to create versions with increased or decreased facial contrast. The set was designed to imitate the differences in facial contrast between older and younger adult faces (Porcheron et al, 2013;Porcheron et al, 2017). This was achieved by modifying the luminance and color of the eyebrows, eyes, and lips while leaving the rest of the face-including the skin-unchanged.…”
Section: Stimulimentioning
confidence: 99%
“…In particular, horizontally oriented contrast (Dakin & Watt, 2009;Goffaux & Dakin, 2010;Pachai, Sekuler, & Bennett, 2013) around the eye/eyebrow and lip regions (Ohayon, Freiwald, & Tsao, 2012;Sinha, 2002) has been shown to be broadly important for face processing and the selectivity of face-specific neurons. The contrast between facial features and the surrounding skin, termed facial contrast, is a cue for perceiving age (Porcheron, Mauger, & Russell, 2013;Porcheron et al, 2017), sex (Jones, Russell, & Ward, 2015;Russell, 2009), attractiveness (Russell, 2003;Störmer & Alvarez, 2016), and health (Russell et al, 2016) from the face, and is modified by typical applications of makeup (Etcoff, Stock, Haley, Vickery, & House, 2011;Jones et al, 2015;Russell, 2009;Stephen & McKeegan, 2010). These face-specific patterns of contrast are related to the distinctive midrange band of spatial frequencies that underlie face perception (Keil, 2008;Näsänen, 1999).…”
Section: Introductionmentioning
confidence: 99%